Índice de qualidade da mobilidade urbana a pé para pessoas idosas (IQMUI) - Silva Filho, Nivaldo Gerôncio da (Universidade Federal de São Carlos, 2016)
Especially you can see that planning not just urban mobility but of infrastructure linked to it, is the result of a great debate and discussion. The impetus given by the mobility in recent years, has taken such a high proportion that affects all modes ratings. Thus, the debate and the discussion ran high, especially from the 1970s and 1980s, when urban problems started to become more evident, because of the swelling of cities and therefore the lack of adequate infrastructure to meet all the wants and needs of the population. It is true that the displacement requirements are supported by law and concerns a right guaranteed, which is to come and go. Due to the fragility of planning, several problems began to emerge in urban areas among which the gaps in the interpretation of responsibilities between the three spheres federal, state and municipal government; and priority when the execution, which in the case of Brazil adopted the exclusionary model of motorized displacement means at the expense of non-motorized. Moreover, even in cases where there is a structure for the foot displacement, this is sometimes precarious especially in medium and large cities. To make the most critical issue in such circumstances arises an aggravating is the rather sharp increase in the elderly population in Brazil, which need special care when it comes to urban infrastructure, particularly walkways and driveways, as this population is characterized among others aspects of weaknesses that are directly linked to displacement. In other words, to the pedestrian does not have mobility problems the infrastructure is already precarious, for the elderly aggravating are significant to the point of making the displacement of this population almost impossible. The set associated with shifts in sidewalks, driveways and crossings are analyzed as a whole may even have satisfactory concepts, but when viewed individually could reach worry levels. In response to these needs, the main objective of this thesis is to propose, in order to improve planning in regard to walkways and driveways, an index to estimate the quality of walkways and driveways facing the elderly population, through 14 indicators divided by 3 groups of subjects. After a comprehensive literature review that brings together different areas of knowledge, it proposed a methodology that initially provides for the incorporation of the opinion of many experts, through a questionnaire. So that the responses to the questionnaire were informed due to some peculiar characteristics of the elderly segment. Pursuant to the case study in a medium-sized city, in general, the results obtained with the index established by the model, have proved to be satisfactory. In conclusion, even considering as a satisfactory result the methodology indicates that it is necessary to provide improvements to walkways and driveways, as the elderly segment requires more appropriate structures.
Keywords: Índice; Mobilidade urbana; Idosos; Poder público; Espaço urbano; Index; Urban mobility; Senior; Government; Urban space; ENGENHARIAS::ENGENHARIA CIVIL